2009
DOI: 10.1093/jnci/djp287
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Prostate Cancer Risk Loci in a Japanese Case–Control Association Study

Abstract: These results highlight the critical importance of considering ancestry in understanding how risk alleles influence disease and suggest that risk estimates and variants differ across populations. It is important to perform studies in multiple ancestral populations so that the composite genetic architecture of prostate cancer can be rigorously addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 14 publications
5
54
0
Order By: Relevance
“…As of this writing, one PCa GWAS has been performed for each of African and Asian ancestries (8,9). Replication studies for variants discovered in European populations have also been performed in these populations (22)(23)(24)(25)(26)(27)(28). The 10q, 17q, and Xp variants (rs10993994, rs4430796, and rs5945619) are associated with PCa risk in men of European, Japanese, and African ancestries (8,(23)(24)(25), and these polymorphisms are also associated with MSMB, NCOA4, HNF1B, and NUDT11 transcripts across all three ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…As of this writing, one PCa GWAS has been performed for each of African and Asian ancestries (8,9). Replication studies for variants discovered in European populations have also been performed in these populations (22)(23)(24)(25)(26)(27)(28). The 10q, 17q, and Xp variants (rs10993994, rs4430796, and rs5945619) are associated with PCa risk in men of European, Japanese, and African ancestries (8,(23)(24)(25), and these polymorphisms are also associated with MSMB, NCOA4, HNF1B, and NUDT11 transcripts across all three ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Witte also mentions his own work with prostate cancers. A GWA study involving 1300 Japanese men has confirmed 7 of 23 SNPs previously implicated in prostate cancer in European populations, but it reminds us that ethnicity and ancestry are important variables in disease association studies (26).…”
Section: The 2010 Symposiummentioning
confidence: 98%
“…Summaries of the 16 final studies (Gudmundsson et al, 2007b;Thomas et al, 2008;Sun et al, 2008a,b;Levin et al, 2008;Waters et al, 2009;Penney et al, 2009;Yamada et al, 2009;Helfand et al, 2009Helfand et al, , 2010Hooker et al, 2010;Zhou et al, 2011;Liu et al, 2011;Kim et al, 2011;Lange et al, 2012;Chan et al, 2012), comprised of 30 datasets collectively, are presented in Table 1. Ethnic groups among these datasets were distributed as follows: within 12 datasets 12,038 cases and 11,938 controls were AW; within 7 datasets 8916 cases and 9401 controls were EW; within 6 datasets 2188 cases and 2477 controls were A; and within 3 datasets 1678 cases and 1229 controls were AA.…”
Section: Characteristics Of Reviewed Studiesmentioning
confidence: 99%
“…Of these variants, the G to A 17q12 rs4430796 polymorphism in HNF1β, the one most often associated with both prostate cancer and diabetes mellitus, has been investigated in an increasing number of studies, including several that evaluated its relationship with prostate cancer risk. Molecular epidemiological studies, however, have yielded contradic tory results concerning the potential role of polymorphism rs4430796 in prostate cancer, especially among diverse populations (Gudmundsson et al, 2007b;Thomas et al, 2008;Sun et al, 2008a,b;Levin et al, 2008;Waters et al, 2009;Penney et al, 2009;Yamada et al, 2009;Helfand et al, 2009Helfand et al, , 2010Hooker et al, 2010;Zhou et al, 2011;Liu et al, 2011;Kim et al, 2011;Lange et al, 2012;Chan et al, 2012). Some of these reports evaluated this association in a variety of races including American white (AW), European white (EW), African-American (AA), Latin-American (LA), and Asian (A).…”
Section: Introductionmentioning
confidence: 99%